QM and ONIOM studies on thermally activated delayed fluorescence of copper(i) complexes in gas phase, solution, and crystal. Issue 38 (21st September 2018) - Gao, Yuan-Jun; Chen, Wen-Kai; Wang, Zi-Rui; Fang, Wei-Hai; Cui, Ganglong
Abstract : QM and ONIOM studies reveal the thermally activated delayed fluorescence mechanism of two Cu(i ) complexes. Abstract : Herein, we have employed B3LYP and TD-B3LYP methods with the QM/MM approach to study the thermally activated delayed fluorescence (TADF) phenomenon of two Cu(i ) complexes bearing 5-(2-pyridyl)-tetrazolate (PyrTet) and phosphine (POP) ligands in the gas phase, solution, and crystal form. On the basis of spectroscopic properties, ground- and excited-state geometric and electronic structures, and related radiative and nonradiative rates, we have found that (1) the S1 and T1 excited states have clear metal-to-ligand charge transfer character from the Cu(i ) atom to the PyrTet group; (2) the S1 and T1 states have a very small energy gap Δ E S1–T1, less than 0.18 eV, which makes the forward and reverse intersystem crossing ISC and rISC processes between the S1 and T1 states very efficient; and (3) the low-frequency vibrational modes related to the torsional motion of the POP and PyrTet groups are found to have significant Huang–Rhys factors and are responsible for the efficient ISC and rISC rates. However, the corresponding Huang–Rhys factors are remarkably suppressed in the crystal compared with those in the gas phase and in solution due to the rigidity of the crystal surroundings; as a result, the ISC and rISC rates are accordingly reduced slightly in the crystal. This comparison also demonstrates that the surrounding effects are very important for modulating the photophysical properties of the Cu(i ) complexes. Finally, our work gives helpful insights into the TADF mechanism of the Cu(i ) compounds, which could assist in rationally designing TADF materials with excellent performance.